2018
DOI: 10.1088/1361-6560/aaf30b
|View full text |Cite
|
Sign up to set email alerts
|

Online adaption approaches for intensity modulated proton therapy for head and neck patients based on cone beam CTs and Monte Carlo simulations

Abstract: To develop an online plan adaptation algorithm for intensity modulated proton therapy (IMPT) based on fast Monte Carlo dose calculation and cone beam CT (CBCT) imaging. A cohort of ten head and neck cancer patients with an average of six CBCT scans were studied. To adapt the treatment plan to the new patient geometry, contours were propagated to the CBCTs with a vector field (VF) calculated with deformable image registration between the CT and the CBCTs. Within the adaptive planning algorithm, beamlets were sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(105 citation statements)
references
References 45 publications
1
104
0
Order By: Relevance
“…In general Monte Carlo (MC) calculations have smaller dose calculation uncertainties, especially in areas with large density heterogeneities [57][58][59][60]. However, in online DAPT, time is a critical factor and even with the fastest available proton MC dose calculations [61][62][63][64], a full plan optimization takes ~5 minutes, while analytical algorithms reoptimise the plan within a few seconds [27]. Additionally, the analytical algorithm used in this study has been shown to compare favourably with full Monte Carlo (TOPAS) dose calculations, with 97.7% and 91.9% of all voxels agreeing within 5% and 3% for a variety of indications, including lung [65] and the difference between the different dose calculation algorithms were negligible compared to those caused by anatomical changes [22].…”
Section: Discussionmentioning
confidence: 99%
“…In general Monte Carlo (MC) calculations have smaller dose calculation uncertainties, especially in areas with large density heterogeneities [57][58][59][60]. However, in online DAPT, time is a critical factor and even with the fastest available proton MC dose calculations [61][62][63][64], a full plan optimization takes ~5 minutes, while analytical algorithms reoptimise the plan within a few seconds [27]. Additionally, the analytical algorithm used in this study has been shown to compare favourably with full Monte Carlo (TOPAS) dose calculations, with 97.7% and 91.9% of all voxels agreeing within 5% and 3% for a variety of indications, including lung [65] and the difference between the different dose calculation algorithms were negligible compared to those caused by anatomical changes [22].…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that a fast plan optimization with MC would be preferable. However, even though recent developments achieved large improvements for the speed of proton MC dose calculations (29,(42)(43)(44), a full plan optimization takes ~5 minutes and is therefore still much slower than analytical approaches, which only take some seconds (30). In an on-line daily adaptive approach the calculation time is a critical factor, therefore for this application an ultra-fast analytical approach is preferable.…”
Section: Discussionmentioning
confidence: 99%
“…Current adaption protocols are however time and resource consuming. Times required for re-planning using MC optimization, which take 5 minutes or more at best, are incompatible with daily online adaption and a high throughput patient workflow (28,29). Re-planning using an analytical algorithm on the other hand can be extremely time efficient, reducing the complete re-planning process to just a few seconds (30), enabling rapid plan adaption on a daily basis.…”
Section: Introductionmentioning
confidence: 99%
“…Users of CBCT should ensure that their CBCT system has adequate image quality for daily image guidance of intensity‐modulated proton therapy (IMPT). Recently, Botas et al developed an online plan adaptation algorithm for IMPT based on fast Monte Carlo dose calculation and CBCT imaging . Those authors concluded that clinical implementation of their developed algorithm would allow adaptation of dose delivery immediately before treatment, thereby allowing planning margins for IMPT to be reduced.…”
Section: Discussionmentioning
confidence: 99%